Digitalisation of criminal justice in the EU through eu-LISA cooperation with Eurojust and Europol: between extraordinary potential and persistent opacity - Valentina Faggiani (UNIO – EU Law Journal, 2024)
The digitalisation of judicial cooperation in criminal matters and police cooperation has become one of the priorities of the EU strategy on e-Justice. The heart of this system is eu-LISA, the European Union Agency for the Operational Management of Large-Scale IT Systems in the Area of Freedom, Security and Justice, and the collaborative relationship it has managed to establish with other bodies in this field, in particular Eurojust and Europol. For this very reason, after examining the role of eu-LISA, this document will focus on the main legislative instruments adopted in the Union to promote this process, which place this Agency at the centre.